PENGEMBANGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS APLIKASI TRACKER UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA - Marina Chandramidi (Universitas Terbuka, 2022)
The purpose of this study is expected to produce a learning model that is more in line with the needs of the Physics learning process. The type of research that will be used in this research is Research and Development. The model development process follows the Borg and Gall development model which consists of ten stages, namely research and data collection, planning, development of initial product drafts, initial field trials, revisions test results, main product field tests, product revisions, wide-scale field trials/feasibility tests, final product revisions, and finally the dissemination and implementation stages. Based on the results of the survey and student test scores, there was an increase in conceptual understanding of the free fall motion material using the PBL learning model based on the Tracker application. So it can be concluded that the PBL learning model based on the Tracker Application is able to improve understanding of Physics concepts in the free fall motion material.